Clinical Efficacy of Patients With Secondary Bacteremia Treated With Omadacycline: Results From Phase 3 Acute Bacterial Skin and Skin Structure Infections and Community-Acquired Bacterial Pneumonia Studies. (18th June 2021) - Sakoulas, George; Eckburg, Paul B; Amodio-Groton, Maria; Manley, Amy; Tzanis, Evan; Das, Anita F; Noble, Robert; McGovern, Paul C
Abstract: In this post hoc analysis of the 63 patients with secondary bacteremia enrolled in the 3 omadacycline phase 3 studies of acute bacterial skin/skin structure infections (ABSSSI) and community-acquired bacterial pneumonia (CABP), we determined that omadacycline is a viable therapeutic option for appropriate patients with secondary bacteremia.